An update on the importance of plasma protein binding in drug discovery and development. (2nd December 2021) - Di, Li
ABSTRACT: Introduction: Plasma protein binding (PPB) remains a controversial topic in drug discovery and development. Fraction unbound (fu ) is a critical parameter that needs to be measured accurately, because it has significant impacts on the predictions of drug-drug interactions (DDI), estimations of therapeutic indices (TI), and developments of PK/PD relationships. However, it is generally not advisable to change PPB through structural modifications, because PPB on its own has little relevance for in vivo efficacy. Areas covered: PPB fundamentals are discussed including the three main classes of drug binding proteins (i.e., albumin, alpha1-acid glycoprotein, and lipoproteins) and their physicochemical properties, in vivo half-life, and synthesis rate. State-of-the-art methodologies for PPB are highlighted. Applications of PPB in drug discovery and development are presented. Expert opinion: PPB is an old topic in pharmacokinetics, but there are still many misconceptions. Improving the accuracy of PPB for highly bound compounds is an ongoing effort in the field with high priority. As the field continues to generate high quality data, the regulatory agencies will increase their confidence in our ability to accurately measure PPB of highly bound compounds, and experimental fu values below 0.01 will more likely be used for DDI predictions in the future.